Resistance to maxillary premolar fractures after restoration of class II preparations with resin composite or ceromer. - Freitas, Cláudia Regina Buainain de; Miranda, Maria Isabel Serra; Andrade, Marcelo Ferrarezi de [UNESP]; Flores, Victor Humberto Orbegoso; Vaz, Luis Geraldo [UNESP]; Guimarães, Catanzaro (My University, 2002)
OBJECTIVE: The aim of this study was to evaluate the resistance to fracture of intact and restored human maxillary premolars. METHOD AND MATERIALS: Thirty noncarious human maxillary premolars, divided into three groups of 10, were submitted to mechanical tests to evaluate their resistance to fracture. Group 1 consisted of intact teeth. Teeth in group 2 received mesio-occlusodistal cavity preparations and were restored with direct resin composite restorations. Teeth in group 3 received mesio-occlusodistal cavity preparations and were restored with ceromer inlays placed with the indirect technique. After restoration, teeth were stored at 37 degrees C for 24 hours and then thermocycled for 500 cycles at temperatures of 5 degrees C and 55 degrees C. RESULTS: Statistical analysis revealed that group 3 (178.765 kgf) had a significantly greater maximum rupture load than did group 1 (120.040 kgf). There was no statistically significant difference between groups 1 and 2 or between groups 2 and 3. CONCLUSION: Class II cavity preparations restored with indirect ceromer inlays offered greater resistance to fracture than did intact teeth. The fracture resistance of teeth restored with resin composite was not significantly different from that of either the ceromer or intact teeth.
Keywords: ceromer; dentin bonding agent; EnForce Sure Cure; EnForce-Sure Cure; Filtek Z250; OptiBond Solo Plus; resin; resin cement; Solidex; analysis of variance; ceramics; chemistry; classification; clinical trial; controlled clinical trial; controlled study; dental acid etching; dental surgery; human; maxilla; mechanical stress; methodology; pathophysiology; premolar tooth; randomized controlled trial; statistics; surface property; temperature; thermodynamics; time; tooth brushing; tooth fracture; Acid Etching, Dental; Analysis of Variance; Bicuspid; Ceramics; Composite Resins; Dental Cavity Preparation; Dental Polishing; Dental Restoration, Permanent; Dentin-Bonding Agents; Humans; Inlays; Maxilla; Resin Cements; Statistics; Stress, Mechanical; Surface Properties; Temperature; Thermodynamics; Time Factors; Tooth Fractures